Protocol for fecal microbiota transplantation: A microaerophilic approach for mice housed in a specific pathogen-free facility - Shari Wouters; Hugo Moors; Mieke Verslegers; Natalie Leys; Surbhi Malhotra-Kumar; Samir Kumar-Singh; Mohamed Mysara (STAR Protocols)
Summary: Recently, studies have emerged exploring the potential application of fecal microbiota transplantation (FMT) in pre-clinical settings. Here, we present a protocol for FMT for mice housed in a specific pathogen-free (SPF) facility. We describe steps for sample collection, microaerophilic processing of freshly collected fecal pellets, and administration through oral gavage. We then detail procedures for the engraftment of the bacterial community. This protocol focuses on age- and gender-matched, healthy donor mice using a mobile and cost-effective alternative to an anoxic cabinet. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.